High-nickel positive electrode material, preparation method thereof and lithium ion battery
Patent Information
- Application Number
- CN202211635181.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-12-19
AI Technical Summary
[0004]目前大多数传统包覆涂层虽起到保护基体材料的作用,但仍然无法解决颗粒间存在大的接触电阻的问题
[0059]本申请提供的高镍正极材料,基体材料表面具有包覆层,包覆层包括含过渡金属的氧化物和碳材料的复合物,可以避免基体材料与电解液的直接接触,有效降低材料表面的残碱,提高正极材料涂层的界面稳定性;包覆层的存在提升了基体材料的电导率并增强锂离子迁移速率;另外,部分高镍正极材料通过包覆层中的碳材料连接形成二级颗粒,能够极大程度地降低颗粒间接触电阻,从而改善高镍正极材料的电子及锂离子导电性能,降低电池电极中的过电位,从而协同增强正极材料循环性能、倍率性能、缓解产气及降低材料的直流阻抗。
Smart Images

Figure CN116190595B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cathode material technology, and particularly relates to a high-nickel cathode material and its preparation method, and lithium-ion batteries. Background Technology
[0002] Currently, high energy density, high operating voltage, long cycle life, and high safety are urgent requirements for the widespread and large-scale application of lithium-ion batteries. The cathode material has a direct and dominant impact on the performance of lithium-ion battery packs; its performance directly affects the overall performance of the lithium-ion battery. Therefore, the development of cathode materials with excellent performance is urgently needed. High-nickel ternary cathode material LiMO2 (where M is typically Ni, Co, Mn, or Al, with a Ni molar fraction above 0.6) is favored due to its high specific capacity (200 mAh g / g). -1 Due to its high packing density and low cost, it has become one of the most feasible options. However, as the nickel content increases, its discharge capacity increases proportionally, but it is accompanied by a series of defects such as rapid capacity decay, structural instability, deterioration of thermal performance, and high residual alkali, which limit its commercial application.
[0003] The main reasons for the performance degradation of high-nickel ternary cathode materials are bulk structure degradation and interfacial side reactions. At the same time, there is a large contact resistance between particles, which further reduces the physicochemical properties. Doping and coating modification are among the most commonly used methods to improve the performance of ternary materials. Among them, coating modification can reduce residual alkali on the material surface, effectively slow down the side reactions between the electrolyte and the material surface, and thus suppress the problems of surface phase transformation and O2 release, thereby improving the structural stability of the material and extending the material life.
[0004] While most traditional coatings currently serve to protect the substrate material, they still cannot solve the problem of high contact resistance between particles. High resistance leads to high overpotentials, resulting in a decrease in the material's rate performance or usable capacity. Summary of the Invention
[0005] The purpose of this application is to provide a high-nickel cathode material and its preparation method, as well as a lithium-ion battery. Some of the high-nickel cathode material particles in this application are connected by a coating layer, which reduces the contact resistance between particles, improves the electronic and lithium-ion conductivity of the high-nickel cathode material, reduces the overpotential in the battery electrode, and improves its cycle performance and rate performance.
[0006] In a first aspect, this application discloses a high-nickel cathode material, said high-nickel cathode material comprising:
[0007] The matrix material has the general chemical formula Li. a Ni x Co y M z N bO2, where 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, x+y+z=1, 0≤b<0.4, M is Mn and / or Al, N comprises at least one of Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba and Ta; and
[0008] a coating layer at least partially located on the surface of the base material, wherein the coating layer comprises a composite, and the composite comprises an oxide of a transition metal and a carbon material, and the transition metal comprises at least one of Co, Ni and Zn;
[0009] wherein at least part of the high-nickel positive electrode material particles are connected through the carbon material in the coating layer to form secondary particles.
[0010] In some embodiments, the thickness of the coating layer is 2 nm to 15 nm.
[0011] In some embodiments, at least part of the oxide of the transition metal is embedded in the carbon material with a porous structure.
[0012] In some embodiments, the coating layer is a composite.
[0013] In some embodiments, the carbon material comprises at least one of an amorphous carbon material and a graphitized carbon material.
[0014] In some embodiments, the high-nickel positive electrode material is connected through C-C conjugated π bonds to form secondary particles.
[0015] In some embodiments, the quantity proportion of the secondary particles in the high-nickel positive electrode material is ε, and 12%<ε<36%.
[0016] In some embodiments, in the high-nickel positive electrode material, CO3 2- has a mass content of P1 wt%, and after the high-nickel positive electrode material is left to stand in air for 7 days, CO3 2- has a mass content of P2 wt%, and 1<P2 / P1<3.
[0017] In some embodiments, the powder conductivity of the high-nickel positive electrode material under a pressure of 8 kN / cm 2 is σ S / cm, 0.3<σ / ε<0.6, and σ>0.06.
[0018] In some embodiments, the specific surface area of the high-nickel positive electrode material is 0.2 m 2 / g to 1.8 m 2 / g.
[0019] In some embodiments, the average particle size D of the high-nickel positive electrode material50 is 8 μm to 25 μm.
[0020] In a second aspect, the present application provides a method for preparing a high-nickel positive electrode material, comprising the following steps:
[0021] Preparing two portions of mixed solutions containing dopamine hydrochloride, a base material and a solvent, wherein the chemical general formula of the base material is Li a Ni x Co y M z N b O₂, wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, x+y+z=1, 0<b<0.4, M is Mn and / or Al, and N includes at least one of Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba and Ta;
[0022] Adding a solution containing transition metal ions to one of the mixed solutions, mixing thoroughly, and performing solid-liquid separation to obtain a first precursor; and adding an organic ligand to the other mixed solution, mixing thoroughly, and performing solid-liquid separation to obtain a second precursor; and
[0023] Adding the mixture of the first precursor and the second precursor into an aqueous solution to carry out a coordination reaction, drying the reaction product, and sintering the reaction product under a protective atmosphere to obtain the high-nickel positive electrode material.
[0024] In some embodiments, the average particle size D of the base material 50 is 9 μm to 18 μm.
[0025] In some embodiments, the mass ratio of the base material to the solvent in the mixed solution is 1:(0.5 to 3).
[0026] In some embodiments, the mass ratio of the base material to dopamine hydrochloride in the mixed solution is 1:(0.01 to 0.4).
[0027] In some embodiments, the solvent includes at least one of water, methanol, ethanol and ethylene glycol.
[0028] In some embodiments, the mixed solution further comprises tris(hydroxymethyl)aminomethane.
[0029] In some embodiments, the mixed solution further comprises tris(hydroxymethyl)aminomethane, and the mass ratio of tris(hydroxymethyl)aminomethane to dopamine hydrochloride is (0.01 to 0.2):1.
[0030] In some embodiments, the pH value of the mixed solution is 8 to 8.5.
[0031] In some embodiments, the transition metal ion includes Co. 2+ Ni 2+ and Zn 2+ At least one of them.
[0032] In some embodiments, the solution containing transition metal ions includes at least one of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt fluoride, cobalt bromide, cobalt iodide, cobalt oxalate, and cobalt sulfate.
[0033] In some embodiments, the mass ratio of the solution containing transition metal ions to the dopamine hydrochloride is (30-80):1, and the mass content of transition metal ions in the solution containing transition metal ions is 1% to 10%.
[0034] In some embodiments, the organic ligand includes at least one of 2-methylimidazole, 2,5-dihydroxyterephthalic acid, and dimethyl 2,5-dioxo-1,4-phthalate.
[0035] In some embodiments, the organic ligand is 2-methylimidazole, and the mass ratio of the 2-methylimidazole to the dopamine hydrochloride is (1-4):1.
[0036] In some embodiments, the mixing temperature is 10°C to 30°C.
[0037] In some embodiments, the mixing time is 0.1 h to 5 h.
[0038] In some embodiments, the solid-liquid separation method includes at least one of filtration and centrifugation.
[0039] In some embodiments, the coordination reaction takes 1 to 8 hours.
[0040] In some embodiments, the temperature of the coordination reaction is 40°C to 80°C.
[0041] In some embodiments, the mass ratio of the first precursor to the second precursor is 1:(0.8 to 1.2).
[0042] In some embodiments, the step of washing the first precursor and the second precursor with water includes adding the first precursor and the second precursor to water respectively, controlling the first stirring rate to be 300 r / min to 600 r / min and stirring and washing for 0.1 h to 3 h, and controlling the second stirring rate to be 10 r / min to 100 r / min and stirring and washing for 0.1 h to 5 h.
[0043] In some embodiments, the total mass of the first precursor and the second precursor is in a weight ratio of 1:(0.5 to 3) to water.
[0044] In some embodiments, the drying temperature is 100℃ to 300℃, and the drying time is 10h to 30h.
[0045] In some embodiments, the sintering temperature is 300℃ to 600℃, and the sintering time is 1h to 6h.
[0046] In some embodiments, the protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.
[0047] In some embodiments, the method further includes Ni x Co y M z oxides or Ni x Co y M z Hydroxide and lithium source are mixed to obtain a mixture, and the mixture is sintered to obtain a matrix material, wherein M is Mn and / or Al.
[0048] In some embodiments, the mixing conditions for obtaining the mixture are: dry grinding at 10°C to 50°C for 0.3h to 2h.
[0049] In some embodiments, the sintering conditions for obtaining the matrix material are as follows: the mixture is pre-sintered at 400℃~600℃ for 3h~9h in an oxygen-containing atmosphere, and then sintered at 650℃~950℃ for 8h~16h.
[0050] In some embodiments, the sintering conditions for obtaining the matrix material are as follows: the mixture is pre-sintered at 400℃~600℃ for 3h~9h in an oxygen-containing atmosphere, and then sintered at 650℃~950℃ for 8h~16h, wherein the mass content of oxygen in the oxygen-containing atmosphere is ≥95%.
[0051] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate, and lithium oxalate.
[0052] In some embodiments, the amount of lithium source added is such that the ratio of the total molar content of Ni, Co and M to the molar content of Li is 1:(0.95~1.1).
[0053] In some embodiments, the mixture further includes a compound containing a dopant element N, including at least one of Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba, and Ta.
[0054] In some embodiments, the mixture further includes a compound containing a dopant element N, wherein N includes at least one selected from Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba, and Ta, and the compound containing the dopant element N includes at least one selected from oxides of N and hydroxides of N.
[0055] In some embodiments, the mixture further includes a compound containing doped element N, wherein the amount of the compound containing doped element N is such that the ratio of the total molar content of Ni, Co and M to the molar content of N is 1:(0 to 0.4).
[0056] Thirdly, this application provides a lithium-ion battery, the lithium-ion battery including a positive electrode sheet, the positive electrode sheet including the high-nickel positive electrode material described in the first aspect or the high-nickel positive electrode material prepared by the method described in the second aspect.
[0057] In some embodiments, the peel strength σ of the positive electrode sheet T180° It ranges from 6mN / mm to 35mN / mm.
[0058] Compared with the prior art, the present invention has the following advantages:
[0059] The high-nickel cathode material provided in this application has a coating layer on the surface of the substrate material. The coating layer includes a composite of oxides containing transition metals and carbon materials, which can avoid direct contact between the substrate material and the electrolyte, effectively reduce residual alkali on the material surface, and improve the interfacial stability of the cathode material coating. The presence of the coating layer increases the conductivity of the substrate material and enhances the lithium-ion migration rate. In addition, some of the high-nickel cathode material is connected by carbon materials in the coating layer to form secondary particles, which can greatly reduce the contact resistance between particles, thereby improving the electronic and lithium-ion conductivity of the high-nickel cathode material, reducing the overpotential in the battery electrode, and thus synergistically enhancing the cycle performance and rate performance of the cathode material, alleviating gas generation, and reducing the DC impedance of the material.
[0060] The preparation method provided in this application involves preparing a mixed solution of dopamine hydrochloride and a matrix material. A solution containing transition metal ions is added to one portion of the mixed solution. The transition metal ions, in the dopamine hydrochloride-containing mixed solution, react with the matrix material through electrostatic attraction and the attraction of the catechol-rich groups of polydopamine to form a first precursor with transition metal ions on its surface. An organic ligand is added to another portion of the mixed solution. The organic ligand, in the dopamine hydrochloride-containing mixed solution, reacts with the matrix material to form a second precursor with a surface coated with polydopamine and the organic ligand. The polydopamine in both the first and second precursors can… The first and second precursors act as an intermediate adhesion medium to adhere transition metal ions and organic ligands, enhancing the interfacial bonding strength between the coating layer and the matrix material. Finally, the first and second precursors are dispersed in water for a coordination reaction. Transition metal ions on the surface of the first precursor and organic ligands on the surface of the second precursor generate a metal-organic framework material in situ through this coordination reaction. During sintering, the metal-organic framework material is transformed in situ into transition metal oxides and carbon materials. Simultaneously, it can capture residual lithium alkali (LiOH and Li₂CO₃) on the surface of the matrix material, reducing residual alkali on the cathode material surface and inhibiting side reactions and gas generation caused by residual alkali. The sintered cathode material has a coating layer on its surface, comprising a complex of oxygen and carbon materials containing transition metals. Some high-nickel cathode material particles are connected by C-C conjugated π bonds in the carbon material to form secondary particles, constituting a conductive network pathway. This significantly reduces the interfacial contact resistance between particles, improving the material's rate performance and cycle stability. Attached Figure Description
[0061] To more clearly illustrate the technical solutions of the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0062] Figure 1 This is a schematic flowchart illustrating the preparation method of the high-nickel cathode material provided in the embodiments of this application.
[0063] Figure 2 This is a schematic diagram of the surface charge of the matrix material of the high-nickel cathode material prepared in Example 1 of this application.
[0064] Figure 3a This is an electron microscope schematic diagram of the high-nickel cathode material prepared in Example 1 of this application.
[0065] Figure 3b This is an electron microscope schematic diagram of the high-nickel cathode material prepared in Comparative Example 1 of this application.
[0066] Figure 4This is a comparison chart showing the powder conductivity test results of the high-nickel cathode materials prepared in Example 1 and Comparative Example 1 of this application.
[0067] Figure 5 This is a comparison chart showing the capacity retention test results of the high-nickel cathode materials prepared in Example 1 and Comparative Example 1 of this application. Detailed Implementation
[0068] To better understand the technical solution of this application, the embodiments of this application will be described in detail below with reference to the accompanying drawings.
[0069] It should be understood that the described embodiments are merely some, not all, of the embodiments in this application. All other embodiments obtained by those skilled in the art based on the embodiments in this application without inventive effort are within the scope of protection of this application.
[0070] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined with "first" or "second" may explicitly or implicitly include one or more of that feature.
[0071] For ease of understanding of this invention, specific terms have been appropriately defined in this application. Unless otherwise defined herein, the scientific and technical terms used in this invention have the meanings commonly understood by one of ordinary skill in the art to which this invention pertains.
[0072] The main reasons for the performance degradation of high-nickel ternary cathode materials are bulk structure degradation and interfacial side reactions. At the same time, there is a large contact resistance between particles, which further reduces the physicochemical properties. Doping and coating modification are among the most commonly used methods to improve the performance of ternary materials. Among them, coating modification can reduce residual alkali on the material surface, effectively slow down the side reactions between the electrolyte and the material surface, and thus suppress the problems of surface phase transformation and O2 release, thereby improving the structural stability of the material and extending the material life.
[0073] While most traditional coatings currently serve to protect the substrate material, they still cannot solve the problem of high contact resistance between particles. High resistance leads to high overpotentials, resulting in a decrease in the material's rate performance or usable capacity.
[0074] Therefore, this application provides a high-nickel cathode material, the high-nickel cathode material comprising:
[0075] The matrix material has the general chemical formula Li. a Ni x Co y M z N bO2, wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, x+y+z=1, 0≤b<0.4, M is Mn and / or Al, and N includes at least one of Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba and Ta; and
[0076] a coating layer at least partially located on the surface of the base material, wherein the coating layer comprises a composite, and the composite comprises a transition metal-containing oxide and a carbon material, the transition metal comprising at least one of Co, Ni and Zn;
[0077] wherein at least part of the high-nickel positive electrode material particles are connected through the carbon material in the coating layer to form secondary particles.
[0078] In the high-nickel positive electrode material provided by the present application, a coating layer is provided on the surface of the base material, and the coating layer comprises a composite of a transition metal-containing oxide and a carbon material, which can avoid direct contact between the base material and the electrolyte, effectively reduce residual alkali on the surface of the material, and improve the interface stability of the positive electrode material coating; the presence of the coating layer improves the conductivity of the base material and enhances the lithium ion migration rate; in addition, part of the high-nickel positive electrode material is connected through the carbon material in the coating layer to form secondary particles, which can greatly reduce the contact resistance between particles, thereby improving the electronic and lithium ion conductivity of the high-nickel positive electrode material, reducing the overpotential in the battery electrode, so as to synergistically enhance the cycle performance and rate performance of the positive electrode material, alleviate gas production and reduce the direct current impedance of the material.
[0079] Specifically, the value of a may be, for example, 0.95, 0.98, 1.01, 1.02, 1.03, 1.05 or 1.1, etc. When the molar content of Li in the high-nickel positive electrode material is within the above range, a battery using the high-nickel positive electrode material has a high charge-discharge specific capacity; when the molar content of Li in the high-nickel positive electrode material is low, Ni tends to enter the Li layer, and cation mixing is obvious, resulting in poor stability of electrochemical cycles. When the molar content of Li in the positive electrode material is high, excess residual alkali will be formed on the surface of the material, which easily forms a jelly-like state during the slurry preparation process and affects the coating effect; secondly, the influence of residual alkali on the electrochemical performance is mainly reflected in the increase of irreversible capacity loss and the deterioration of cycle performance at the same time.
[0080] The value of x can be, for example, 0.6, 0.7, 0.8, 0.85, 0.86, 0.87, 0.88, 0.9, 0.92, 0.95, 0.97, or 0.99, etc.; the value of y can be, for example, 0.01, 0.05, 0.08, 0.1, 0.15, 0.16, 0.18, 0.2, 0.3, 0.37, or 0.39, etc.; and the value of z can be, for example, 0.01, 0.05, 0.08, 0.1, 0.15, 0.16, 0.18, 0.2, 0.3, 0.37, or 0.39, etc., without limitation. When the total molar content of Ni, Co, and M in the cathode material is within the above range, the battery exhibits good electrochemical performance. When the total molar content of Ni, Co, and M in the cathode material is low, the battery has a high initial irreversible capacity but poor cycle and rate performance; when the total molar content of Ni, Co, and M in the cathode material is high, the battery has a low capacity that cannot meet the energy density requirements, affecting practical applications.
[0081] The value of b can be, for example, 0, 0.01, 0.05, 0.1, 0.2, 0.3, 0.35, or 0.39, etc.
[0082] In some embodiments, the composite is obtained by carbonizing a metal-organic framework material containing a transition metal and polydopamine. It should be noted that metal-organic frameworks (MOFs) are porous crystalline materials formed by the coordination of organic ligands and metal ions or ion clusters through metallic bonds.
[0083] In some embodiments, the coating layer is a composite.
[0084] In some embodiments, the carbon material includes at least one of amorphous carbon material and graphitized carbon material.
[0085] In some embodiments, the carbon material has a porous structure. Understandably, the porous structure of the metal-organic framework material allows the carbon material to retain its porous structure after carbonization; this porous structure can alleviate stress and strain, maintaining the structural stability of the material.
[0086] In some embodiments, at least a portion of the transition metal oxide is embedded in the carbon material having a porous structure. The dispersion of the transition metal oxide in the coating layer improves the conductivity of the cathode material, forming a conductive network on the surface of the cathode material and reducing the interfacial contact resistance between particles.
[0087] In some embodiments, the high-nickel cathode material is connected by C-C conjugate π bonds to form secondary particles. It should be noted that the secondary particles can be formed by connecting two adjacent high-nickel cathode material particles, or by connecting three or more high-nickel cathode material particles. To avoid affecting the coating performance of the cathode material, it is preferable to use secondary particles formed by connecting two adjacent high-nickel cathode material particles. This reduces the interparticle interface resistance while minimizing impact on the particle size and processing performance of the cathode material.
[0088] In some embodiments, the proportion of the secondary particles in the high-nickel cathode material is ε, where 12% < ε < 36%. Specifically, the value of ε can be 12.1%, 12.6%, 13.5%, 15.9%, 16.6%, 18.5%, 21.8%, 26.3%, or 35.7%, etc., and is not limited here. It is understood that an appropriate amount of secondary particles can significantly reduce the interparticle contact resistance, thereby improving the electronic and lithium-ion conductivity of the high-nickel cathode material and reducing the overpotential in the battery electrodes.
[0089] In some embodiments, the average particle size of the matrix material is 9 μm to 18 μm; specifically, it can be 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, or 18 μm, or other values within the above range, which are not limited here. Controlling the particle size of the active material within the above range is beneficial to improving the structural stability, thermal stability, and long-cycle stability of the cathode material.
[0090] In some embodiments, the thickness of the coating layer is 2nm to 15nm. Specifically, it can be 2nm, 3nm, 4nm, 5nm, 8nm, 10nm, 12nm, or 15nm, etc., or other values within the above range, which are not limited here. If the coating layer is too thick, it will reduce the activity of the material, hinder contact with the electrolyte, and affect the battery capacity. If the coating layer is too thin, it will reduce the coating effect and fail to block side reactions on the material surface.
[0091] In some embodiments, the coating layer has a porous structure. The porous structure can be micropores and / or nanopores. It should be noted that micropores refer to pore structures with a pore size of less than 2 nm, and nanopores refer to pore structures with a pore size ranging from 1 nm to 100 nm.
[0092] In some embodiments, the average particle size of the high-nickel cathode material is between 8 μm and 25 μm, specifically 8 μm, 8.5 μm, 9 μm, 10 μm, 12 μm, 14 μm, 15 μm, 18 μm, 20 μm, or 25 μm, or other values within the above range, which are not limited here. Controlling the particle size of the cathode material within the above range is beneficial to improving the structural stability, thermal stability, and long-cycle stability of the cathode material.
[0093] In some embodiments, the specific surface area of the high-nickel positive electrode material is 0.2 m 2 / g to 1.8 m 2 / g. Specifically, it may be 0.2 m 2 / g, 0.4 m 2 / g, 0.5 m 2 / g, 0.6 m 2 / g, 0.7 m 2 / g, 1.2 m 2 / g, 1.5 m 2 / g, 1.6 m 2 / g or 1.8 m 2 / g, etc. When the specific surface area of the positive electrode material is controlled within the above range, it is beneficial to improving the cycle performance of the lithium battery made of the positive electrode material.
[0094] In some embodiments, the powder conductivity of the high-nickel positive electrode material under a pressure of 8 kN / cm 2 is σ S / cm, 0.3 < σ / ε < 0.6, and σ > 0.06; specifically, the value of σ may be 0.07 S / cm, 0.08 S / cm, 0.09 S / cm, 0.1 S / cm, 0.2 S / cm, 0.3 S / cm or 0.4 S / cm, etc., and certainly may also be other values within the above range, which can effectively improve the discharge capacity at a high current rate. Specifically, the value of σ / ε may be 0.31, 0.35, 0.38, 0.42, 0.45, 0.48, 0.52, 0.55 or 0.6, etc., and certainly may also be other values within the above range. Controlling the ratio of σ / ε can greatly reduce the interfacial contact resistance of the positive electrode material and improve the powder conductivity.
[0095] In some embodiments, the mass content of CO3 in the high-nickel positive electrode material is P1 wt%, and the high-nickel positive electrode material is left to stand in air for 7 days, the mass content of CO3 2- is P2 wt%, and 1 < P2 / P1 < 3; specifically, P2 / P1 may be 1.01, 1.1, 1.5, 1.8, 2.2, 2.5, 2.8 or 2.99, etc., and certainly may also be other values within the above range. 2-
[0096] The embodiments of the present application provide a preparation method of the high-nickel positive electrode material, as shown Figure 1 , including the following steps:
[0097] Step S10, preparing two portions of mixed solutions containing dopamine hydrochloride, a base material and a solvent;
[0098] In step S20, a solution containing transition metal ions is added to one portion of the mixed solution, after thorough mixing, solid-liquid separation is performed to obtain a first precursor; and an organic ligand is added to the other portion of the mixed solution, after thorough mixing, solid-liquid separation is performed to obtain a second precursor; and
[0099] In step S30, the mixture of the first precursor and the second precursor is added to an aqueous solution for a coordination reaction, and the reaction product is dried and sintered under a protective atmosphere to obtain a high-nickel cathode material.
[0100] wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, x+y+z=1, 0<b<0.4, M is Mn and / or Al, and N includes at least one of Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba and Ta.
[0101] In the above technical solution, by preparing a mixed solution of dopamine hydrochloride and a base material, after adding a solution containing transition metal ions to one portion of the mixed solution, the transition metal ions form a first precursor with transition metal ions on the surface through electrostatic attraction between the transition metal ions and the base material in the mixed solution containing dopamine hydrochloride and the attraction effect of the catechol-rich groups of polydopamine; an organic ligand is added to the other portion of the mixed solution, the organic ligand forms a second precursor coated with polydopamine and the organic ligand on the surface with the base material in the mixed solution containing dopamine hydrochloride, wherein the polydopamine in the first precursor and the second precursor can act as an intermediate adhesion medium to adhere the transition metal ions and the organic ligand, which can enhance the interfacial bonding strength between the coating layer and the base material; finally, the first precursor and the second precursor are washed with water together, the transition metal ions on the surface of the first precursor and the organic ligand on the surface of the second precursor in-situ form a metal-organic framework material through a coordination reaction, during the sintering process, the metal-organic framework material is in-situ converted into transition metal oxide and carbon material, and can simultaneously capture lithium residues (LiOH and Li₂CO₃) on the surface of the base material, reduce the residual alkali on the surface of the cathode material, and inhibit the occurrence of side reactions and gas production caused by the residual alkali. The surface of the cathode material obtained by sintering has a coating layer, the coating layer comprises a composite of transition metal-containing oxide and carbon material, part of the high-nickel cathode material particles are connected through C-C conjugated π bonds of the carbon material to form secondary particles, forming a conductive network path, which significantly reduces the interfacial contact resistance between particles, and improves the rate performance and cycle stability of the material.
[0102] The preparation method of the present application is specifically introduced below with reference to the examples:
[0103] Before step S10, the method further comprises:
[0104] Ni x Coy M z oxides or Ni x Co y M z Hydroxide and lithium source are mixed to obtain a mixture, which is then sintered to obtain a matrix material, wherein M is Mn and / or Al. 0.6≤x<1, 0 <y<0.4,0<z<0.4。
[0105] In some embodiments, the ratio of the total molar content of Ni, Co, and M to the molar content of Li is 1:(0.95 to 1.1), specifically 0.95, 0.99, 1.01, 1.02, 1.03, 1.05, 1.06, 1.08, and 1.1, etc. Controlling the ratio of the total molar content of Ni, Co, and M to the molar content of Li within the above range is beneficial to the formation of matrix material grains and the improvement of material electrochemical performance.
[0106] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate, and lithium oxalate.
[0107] In some embodiments, the mixture further includes a compound containing a dopant element N, including at least one of Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba, and Ta.
[0108] In some embodiments, the compound containing doped element N includes at least one of oxides of element N and hydroxides of element N.
[0109] In some embodiments, the amount of the compound containing the dopant element N is such that the ratio of the total molar content of Ni, Co and M to the molar content of N is 1:(0 to 0.4).
[0110] In some embodiments, the mixing conditions for obtaining the mixture are: dry grinding at 10°C to 50°C for 0.3h to 2h. The specific temperature for dry grinding can be 10°C, 20°C, 30°C, 40°C, and 50°C, or other values within the above range. The specific time for dry grinding can be 0.3h, 0.5h, 0.8h, 1h, 1.5h, or 2h, or other values within the above range.
[0111] In some embodiments, the sintering conditions for obtaining the matrix material are as follows: the mixture is pre-sintered at 400℃~600℃ for 3h~9h in an oxygen-containing atmosphere, and then sintered at 650℃~950℃ for 8h~16h.
[0112] Specifically, the first stage sintering temperature can be 400℃, 420℃, 450℃, 470℃, 480℃, 500℃, 520℃, 550℃, 580℃, and 600℃, or other values within the above range, which are not limited here. The first stage sintering holding time can be 3h, 3.5h, 4h, 5.5h, 6h, 7.5h, or 9h, or other values within the above range, which are not limited here.
[0113] The specific temperatures for the second stage of sintering can be 650℃, 720℃, 750℃, 770℃, 780℃, 800℃, 820℃, 850℃, 880℃, and 920℃, or other values within the above ranges. The specific holding time for the second stage of sintering can be 8h, 10h, 12h, 12.5h, 13h, 15h, or 16h, or other values within the above ranges.
[0114] In some embodiments, the sintering equipment includes a stationary box furnace or a roller kiln-type continuous furnace.
[0115] In some implementations, readily available matrix materials can be purchased directly for coating and modification.
[0116] In some embodiments, the average particle size of the matrix material is 9 μm to 18 μm; specifically, it can be 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, or 18 μm, or other values within the above range, which are not limited here. Controlling the particle size of the active material within the above range is beneficial to improving the structural stability, thermal stability, and long-cycle stability of the cathode material.
[0117] Step S10: Prepare two mixed solutions containing dopamine hydrochloride, matrix material, and solvent.
[0118] In some embodiments, the mass ratio of the matrix material to the solvent in the mixed solution is 1:(0.5-3), specifically 1:0.5, 1:0.8, 1:1, 1:1.5, 1:1.8, 1:2.2, 1:2.5 or 1:3, etc., which are not limited here.
[0119] In some embodiments, the mass ratio of the matrix material to dopamine hydrochloride in the mixed solution is 1:(0.01 to 0.4); specifically, it can be 1:0.01, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3 or 1:0.4, etc., and is not limited here.
[0120] In some embodiments, the solvent includes at least one of water, methanol, ethanol, ethylene glycol, and N,N-dimethylformamide (DMF).
[0121] In some embodiments, the pH of the mixed solution is between 8 and 8.5. This weakly alkaline environment is conducive to the cross-linking reaction of dopamine, forming a polydopamine layer on the surface of the matrix material. An appropriate amount of alkaline solution can be added to the mixed solution to adjust the pH to approximately 8 to 8.5. Specific alkaline solutions can include ammonia, sodium hydroxide solution, potassium hydroxide solution, etc.
[0122] In some embodiments, the mixed solution further includes tris(hydroxymethyl)aminomethane (referred to as tris reagent). The addition of tris reagent is beneficial to the polymerization effect of dopamine at room temperature, thereby generating polydopamine on the surface of the matrix material. Polydopamine has adhesive properties and adheres to the surface of the matrix material to form a polydopamine nanofilm. The polydopamine nanofilm is viscous.
[0123] In some embodiments, the mass ratio of tris(hydroxymethyl)aminomethane to dopamine hydrochloride is (0.01 to 0.2):1, specifically 0.01:1, 0.02:1, 0.05:1, 0.08:1, 0.1:1, 0.15:1 or 0.2:1, etc., which are not limited here.
[0124] Step S20: Add a solution containing transition metal ions to one portion of the mixed solution, mix thoroughly, and then separate the solid and liquid components to obtain the first precursor; and add an organic ligand to the other portion of the mixed solution, mix thoroughly, and then separate the solid and liquid components to obtain the second precursor.
[0125] In the step of adding a solution containing transition metal ions to a portion of the mixed solution, mixing thoroughly, and then separating the solid and liquid to obtain the first precursor, the transition metal ions adhere to the polydopamine on the surface of the matrix material under the adhesive effect of polydopamine and the electrostatic attraction of the OH-rich catechol groups of polydopamine.
[0126] In some embodiments, the transition metal ion includes Co. 2+ Ni 2+ and Zn 2+ At least one of them.
[0127] In some embodiments, the solution containing transition metal ions includes at least one of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt fluoride, cobalt bromide, cobalt iodide, cobalt oxalate, and cobalt sulfate.
[0128] In some embodiments, the solution containing transition metal ions includes at least one of zinc nitrate, zinc acetate, zinc chloride, zinc bromide, zinc oxalate, and zinc sulfate.
[0129] In some embodiments, the solution containing transition metal ions includes at least one of nickel nitrate, nickel acetate, nickel chloride, nickel bromide, nickel iodide, nickel oxalate, and nickel sulfate.
[0130] In some embodiments, the mass ratio of the solution containing transition metal ions to the dopamine hydrochloride is (30-80):1, specifically 30:1, 35:1, 44:1, 56:1, 63:1, 72:1 or 80:1, etc., which are not limited here.
[0131] In some embodiments, the mass content of transition metal ions in the solution containing transition metal ions is 1% to 10%, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7% or 10%, etc., and is not limited here.
[0132] In the step of adding an organic ligand to another portion of the mixed solution, mixing thoroughly, and then separating the solid and liquid to obtain the second precursor, the organic ligand adheres to the polydopamine on the surface of the matrix material under the adhesive effect of polydopamine and the electrostatic attraction effect.
[0133] In some implementations, the organic ligand is first dissolved in a solvent, and then the solution containing the organic ligand is added to the mixed solution, which can improve the homogeneity of the solution system.
[0134] In some embodiments, the organic ligand includes at least one of 2-methylimidazolium, 2,5-dihydroxyterephthalic acid, and dimethyl 2,5-dioxo-1,4-phthalate;
[0135] In some embodiments, the organic ligand is 2-methylimidazole, and the mass ratio of the 2-methylimidazole to the dopamine hydrochloride is (1-4):1; specifically, it can be 1:1, 1.6:1, 2.7:1, 3.3:1 or 4:1, etc., which are not limited here.
[0136] In some embodiments, the mixing temperature is 10°C to 30°C; specific temperatures include 10°C, 15°C, 20°C, 22°C, 25°C, 28°C, 29°C, and 30°C, etc., and of course, other values within the above range are also possible, which are not limited here.
[0137] In some embodiments, the mixing time is 0.1h to 5h; specifically, the mixing time is 0.1h, 0.2h, 0.5h, 1h, 2h, 3h, 4h and 5h, etc., and of course, other values within the above range are also possible, which are not limited here.
[0138] In some embodiments, the solid-liquid separation method includes at least one of filtration and centrifugation. Filtration can be atmospheric pressure filtration, reduced pressure filtration, or vacuum filtration. Preferably, to increase efficiency, vacuum filtration is used for solid-liquid separation.
[0139] Step S30: The mixture of the first precursor and the second precursor is added to an aqueous solution to carry out a coordination reaction, and the reaction product is dried and sintered under a protective atmosphere to obtain a high-nickel cathode material.
[0140] Understandably, dispersing the first and second precursors in water for a coordination reaction allows transition metal ions on the surface of the first precursor to interact with organic ligands on the surface of the second precursor, generating a metal-organic framework (MOF) material in situ. During this coordination reaction, adjacent matrix material particles undergo a bridging effect, bonding together to form secondary particles. Furthermore, the MOF material possesses a porous structure, and some of it adheres to the matrix material surface via polydopamine, mitigating stress and strain, maintaining structural stability, and enhancing the bond strength with the matrix material. Organic ligands and transition metal ions that do not participate in the coordination reaction can also be converted into transition metal oxides and carbon materials during sintering, distributing on the matrix material surface. This prevents electrolyte erosion while enhancing the bulk conductivity of the cathode material, thereby reducing the rate-reduction ratio (DCR) and improving battery rate performance and cycle stability.
[0141] In some embodiments, the temperature of the coordination reaction is 40℃ to 120℃, specifically 40℃, 50℃, 55℃, 60℃, 65℃, 70℃, 80℃, 90℃, 100℃, 110℃ or 120℃, etc., which are not limited here.
[0142] In some implementations, the coordination reaction time is 1h to 8h, specifically 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h, etc., and of course other values within the above range are also possible, which are not limited here.
[0143] In some embodiments, the mass ratio of the first precursor to the second precursor is 1:(0.8 to 1.2), specifically it can be 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.12, 1:1.15, 1:1.17 or 1:1.2, etc., and is not limited here.
[0144] In some embodiments, the step of adding the mixture of the first precursor and the second precursor to an aqueous solution for coordination reaction includes adding the first precursor and the second precursor to water respectively, stirring and washing at a first stirring rate of 300 r / min to 600 r / min for 0.1 h to 3 h, and stirring and washing at a second stirring rate of 10 r / min to 100 r / min for 0.1 h to 5 h.
[0145] Specifically, the first stirring rate can be 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min or 600 r / min; the second stirring rate can be 10 r / min, 20 r / min, 40 r / min, 50 r / min, 60 r / min, 70 r / min or 100 r / min, etc., or other values within the above range, which are not limited here.
[0146] In some embodiments, the total mass of the first precursor and the second precursor is in a weight ratio of water to 1:(0.5 to 3); specifically, it can be 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:2.8 or 1:3, etc., or other values within the above range, which are not limited here.
[0147] In some embodiments, the drying temperature is 100℃~300℃, and the drying time is 10h~30h; the drying temperature can specifically be 100℃, 150℃, 180℃, 200℃, 220℃, 260℃, 280℃ and 300℃, etc., and the drying time can be 10h, 12h, 15h, 17h, 18h, 20h, 25h and 30h, etc., and of course, other values within the above ranges are also possible, which are not limited here.
[0148] Understandably, drying treatment can improve the bonding strength of coatings (polydopamine and metal-organic framework materials) on the surface of the matrix material.
[0149] In some embodiments, the sintering temperature is 300℃~600℃, and the sintering time is 1h~6h; the sintering temperature can specifically be 300℃, 350℃, 400℃, 450℃, 500℃, 560℃, 580℃, and 600℃, etc., and the drying time can be 1h, 2h, 3h, 4h, 5h, and 6h, etc., and of course, other values within the above range are also possible, and are not limited here. During the sintering process, the metal-organic framework material is converted in situ into transition metal oxides and carbon materials, and polydopamine is also converted into carbon materials. At the same time, it can capture lithium residues (LiOH and Li2CO3) on the surface of the matrix material, reduce residual alkali on the surface of the cathode material, and inhibit the occurrence of side reactions and gas generation caused by residual alkali.
[0150] In some embodiments, the protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.
[0151] Understandably, polydopamine possesses strong anchoring power and maintains high stability even after sintering, effectively isolating the electrode from direct contact with the electrolyte and improving the material's conductivity. The metal-organic framework material is in-situ converted into a composite of transition metal oxides and carbon materials. The carbon in the composite connects adjacent particles through conjugated π bonds with the carbon on the particle surface, promoting adhesion between adjacent particles and reducing interfacial contact resistance.
[0152] This application also provides a lithium-ion battery, including a positive electrode, a negative electrode, a separator, a non-aqueous electrolyte, and a casing. The positive electrode includes a current collector and a positive electrode active material coated on the current collector. The positive electrode active material includes a high-nickel positive electrode material as described above or a high-nickel positive electrode material prepared by the preparation method of the high-nickel positive electrode material described above, as well as a conductive agent and a binder.
[0153] In some embodiments, the conductive agent is one of conductive carbon black, Ketjen black, graphite, and acetylene black.
[0154] In some embodiments, the binder is one of sodium carboxymethyl cellulose, cyclodextrin, and polyvinylidene fluoride.
[0155] In some embodiments, the solvent in the positive electrode active material is selected from deionized water, N-methylpyrrolidone, and N,N-dimethylformamide.
[0156] In some embodiments, the peel strength σ of the positive electrode sheet T180° The value ranges from 6 mN / mm to 35 mN / mm. Specifically, it can be 6 mN / mm, 8 mN / mm, 10 mN / mm, 15 mN / mm, 20 mN / mm, 30 mN / mm, or 35 mN / mm, etc., and is not limited here.
[0157] The embodiments of the present invention will be further described below with reference to several examples. However, the embodiments of the present invention are not limited to the specific embodiments described below. Appropriate modifications can be made within the scope of the original claims.
[0158] Example 1
[0159] A method for preparing a high-nickel cathode material includes the following steps:
[0160] (1) Weigh an appropriate amount of LiOH and Ni as a mixture of nickel-cobalt precursor in a molar ratio of 1.04:1. 0.90 Co 0.10(OH)2, and according to Ni 0.90 Co 0.10 The mass ratio of Al(OH)2 to Al(OH)3 is 78:1. Weigh an appropriate amount of Al(OH)3, mix the three powders, and then pulverize and grind them to obtain a mixture.
[0161] (2) The mixture was calcined in a muffle furnace at 550°C for 4 hours, ground into fine particles, and then transferred to a tube furnace for high-temperature sintering in an oxygen atmosphere for 14 hours. The sintering temperature was controlled at 750°C. The sintered matrix material was then pulverized to D... 50 The particle size is approximately 11 μm. The pulverized material is stored in a polyethylene plastic bag and sealed with aluminum-plastic film.
[0162] (3) Add tris(hydroxymethyl)aminomethane (Tris reagent) to a stirrable water-washing reactor and stir to form a solution (pH 8.5). Then add 50g of matrix material and stir for 0.5h. Weigh 0.45g of dopamine hydrochloride and dissolve it in the above suspension. Stir for 1h. Then add 30ml of aqueous solution containing 1.5g of cobalt nitrate and continue stirring for 2h. After that, filter for 20min to obtain the first precursor.
[0163] (4) Add tris(hydroxymethyl)aminomethane (Tris reagent) to a stirrable water-washing reactor and stir to form a solution (pH 8.5) in 70 ml of deionized water. Then add 50 g of matrix material and stir for 0.5 h. Weigh 0.45 g of dopamine hydrochloride and dissolve it in the above suspension. Stir for 1 h. Then add 30 ml of aqueous solution containing 0.9 g of 2-methylimidazole and continue stirring for 2 h. After that, filter for 20 min to obtain the second precursor.
[0164] (5) Add 50g of the first precursor and 50g of the second precursor to 70ml of deionized water. Stir rapidly at 500r / min for 0.5h at room temperature, then stir slowly at 30r / min for 2h. After that, filter the mixed solution in the reactor for 20min. The collected solid part is dried at 100℃ for 30h. Then, the dried material is calcined at 450℃ for 3h in N2 atmosphere to obtain the modified high-nickel cathode material.
[0165] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 O2 and a coating layer, the coating layer including carbon materials and Co-based oxides, the coating layer thickness is 6.3 nm, and the secondary particle quantity ratio ε is 22%; the high-nickel cathode material has an average particle size of 13.2 μm and a specific surface area of 0.76 m².2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.110 S / cm, and the σ / ε ratio is 0.50. The peel strength σ of the electrode sheet prepared from the high-nickel cathode material is... T180° It is 9.8 mN / mm.
[0166] like Figure 2 As shown, the matrix material prepared in this embodiment carries a negative charge on its surface, and Co is attracted by electrostatic attraction. 2+ It will be firmly loaded on the surface of the base material.
[0167] like Figure 3a As shown, the high-nickel cathode material prepared in this embodiment contains some secondary particles, which are formed by the interconnection of adjacent cathode material particles.
[0168] Example 2
[0169] Unlike Example 1, (5) 50g of the first precursor and 50g of the second precursor were added together to 70ml of deionized water. The mixture was stirred rapidly at 500r / min for 0.5h at room temperature, and then slowly stirred at 100r / min for 2h. The mixed solution in the reactor was then filtered for 20min. The collected solid part was dried at 100℃ for 30h to obtain the modified high-nickel cathode material.
[0170] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 O2 and a coating layer, the coating layer including carbon materials and Co-based oxides, the coating layer thickness is 6.0 nm, and the secondary particle quantity ratio ε is 16%; the high-nickel cathode material has an average particle size of 11.6 μm and a specific surface area of 0.82 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.075 S / cm, and the σ / ε ratio is 0.47. The peel strength σ of the electrode prepared from the high-nickel cathode material is... T180° It is 7.3 mN / mm.
[0171] Example 3
[0172] Unlike Example 1, (5) 50g of the first precursor and 50g of the second precursor were added together to 70ml of deionized water. The mixture was stirred rapidly at 500r / min for 0.5h at room temperature, and then slowly stirred at 10r / min for 2h. The mixed solution in the reactor was then filtered for 20min. The collected solid part was dried at 100℃ for 30h to obtain the modified high-nickel cathode material.
[0173] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 O2 and a coating layer, the coating layer including carbon materials and Co-based oxides, the coating layer thickness is 6.8 nm, and the secondary particle quantity ratio ε is 32%; the high-nickel cathode material has an average particle size of 14.5 μm and a specific surface area of 0.79 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.170 S / cm, and the σ / ε ratio is 0.53. The peel strength σ of the electrode sheet prepared from the high-nickel cathode material is... T180° It is 12.5 mN / mm.
[0174] Example 4
[0175] Unlike Example 1, (3) Tris(hydroxymethyl)aminomethane (Tris reagent) was added to a stirrable water-washing reactor and dissolved in 70 ml of deionized water to form a solution (pH 8.5). Then, 50 g of matrix material was added and the reaction was stirred for 0.5 h. 0.45 g of dopamine hydrochloride was weighed and dissolved in the above suspension and the reaction was stirred for 1 h. Then, 30 ml of an aqueous solution containing 1.5 g of zinc nitrate was added and the mixture was stirred for 2 h. After that, the mixture was filtered for 20 min to obtain the first precursor. The subsequent operations were the same as in Example 1.
[0176] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 O2 and a coating layer, the coating layer including carbon materials and Zn-based oxides, the coating layer thickness is 6.6 nm, and the secondary particle quantity ratio ε is 20%; the high-nickel cathode material has an average particle size of 13.9 μm and a specific surface area of 0.71 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.098 S / cm, and the σ / ε ratio is 0.49. The peel strength σ of the electrode prepared from the high-nickel cathode material is... T180° It is 9.5 mN / mm.
[0177] Example 5
[0178] Unlike Example 1, (4) Tris(hydroxymethyl)aminomethane (Tris reagent) was added to a stirrable water-washing reactor and dissolved in 70 ml of deionized water to form a solution (pH 8.5). Then, 50 g of matrix material was added and the reaction was stirred for 0.5 h. 0.45 g of dopamine hydrochloride was weighed and dissolved in the above suspension and the reaction was stirred for 1 h. Then, 30 ml of a solution of N,N-dimethylformamide / ethanol containing 0.9 g of 2,5-dihydroxyterephthalic acid (N,N-dimethylformamide / ethanol volume ratio 2:1) was added and the mixture was stirred for 2 h. After that, the mixture was filtered for 20 min to obtain the second precursor.
[0179] (5) Add 50g of the first precursor and 50g of the second precursor together to 60ml of a mixed solvent of DMF / ethanol (N,N-dimethylformamide / ethanol volume ratio is 3:1). Stir rapidly at 500r / min for 0.5h at room temperature, and then stir slowly at 30r / min for 24h at 120℃. After that, filter the mixed solution in the reactor for 20min, collect the solid part and dry it at 100℃ for 30h. Then calcine the dried material at 450℃ for 3h in N2 atmosphere to obtain the modified high nickel cathode material.
[0180] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 O2 and a coating layer, the coating layer including carbon materials and Co-based oxides, the coating layer thickness is 6.2 nm, and the secondary particle quantity ratio ε is 19%; the high-nickel cathode material has an average particle size of 13.2 μm and a specific surface area of 0.73 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.092 S / cm, and the σ / ε ratio is 0.48. The peel strength σ of the electrode sheet prepared from the high-nickel cathode material is... T180° It is 9.1 mN / mm.
[0181] Example 6
[0182] Unlike Example 1, NCM811 nickel cobalt manganese oxide lithium matrix material was purchased directly from the market, and the modified high-nickel cathode material was obtained by using the same scheme of steps (3)(4)(5).
[0183] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.00 Ni 0.80 Co 0.10 Mn 0.10O2 and a coating layer, the coating layer including carbon materials and Co-based oxides, the coating layer thickness is 6.6 nm, and the secondary particle quantity ratio ε is 23%; the high-nickel cathode material has an average particle size of 13.2 μm and a specific surface area of 0.76 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.115 S / cm, and the σ / ε ratio is 0.50. The peel strength σ of the electrode sheet prepared from the high-nickel cathode material is... T180° It is 9.9 mN / mm.
[0184] Example 7
[0185] Unlike Example 1, (3) 70 ml of deionized water was added to a stirrable water-washing reactor, and ammonia was added to adjust the pH of the aqueous solution to 8.5. Then 50 g of matrix material was added, and the reaction was stirred for 0.5 h. 0.45 g of dopamine hydrochloride was weighed and dissolved in the above suspension, and the reaction was stirred for 1 h. Then 30 ml of an aqueous solution containing 1.5 g of cobalt nitrate was added, and the mixture was stirred for 2 h. After that, the mixture was filtered for 20 min to obtain the first precursor.
[0186] (4) Add 70 ml of deionized water to a stirrable water-washing reactor and add ammonia to adjust the pH of the aqueous solution to 8.5. Then add 50 g of matrix material and stir for 0.5 h. Weigh 0.45 g of dopamine hydrochloride and dissolve it in the above suspension. Stir for 1 h. Then add 30 ml of aqueous solution containing 0.9 g of 2-methylimidazole and continue stirring for 2 h. After that, filter for 20 min to obtain the second precursor.
[0187] Subsequent operations are the same as in Example 1.
[0188] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 O2 and a coating layer, the coating layer including C and Co-based oxides, the coating layer thickness is 6.5 nm, and the secondary particle quantity ratio ε is 24%; the high-nickel cathode material has an average particle size of 13.4 μm and a specific surface area of 0.73 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.122 S / cm, and the σ / ε ratio is 0.51. The peel strength σ of the electrode sheet prepared from the high-nickel cathode material is... T180° It is 10.1 mN / mm.
[0189] Example 8
[0190] Unlike Example 1, (1) an appropriate amount of LiOH and the binary material nickel-cobalt precursor Ni were weighed in a molar ratio of 1.04:1. 0.90 Co 0.10 (OH)2, and according to Ni 0.90 Co 0.10 Weigh out an appropriate amount of Al(OH)3 with a mass ratio of (OH)2 to Al(OH)3 of 78:1. Furthermore, according to Ni… 0.90 Co 0.10 Weigh out an appropriate amount of Zr(OH)4 with a mass ratio of 350:1 for Zr(OH)2 and Zr(OH)4. Mix the four powders and grind them to obtain a mixture. Subsequent operations are the same as in Example 1.
[0191] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.883 Co 0.096 Al 0.018 Zr 0.003 O2 and a coating layer, the coating layer including carbon materials and Co-based oxides, the coating layer thickness is 6.9 nm, and the secondary particle quantity ratio ε is 21%; the high-nickel cathode material has an average particle size of 13.7 μm and a specific surface area of 0.73 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.106 S / cm, and the σ / ε ratio is 0.50. The peel strength σ of the electrode prepared from the high-nickel cathode material is... T180° It is 9.3 mN / mm.
[0192] Example 9
[0193] Unlike Example 1, (5) 50g of the first precursor and 40g of the second precursor were added together to 70ml of deionized water. The mixture was stirred rapidly at 500r / min for 0.5h at room temperature, and then slowly stirred at 30r / min for 2h. The mixed solution in the reactor was then filtered for 20min. The collected solid part was dried at 100℃ for 30h. The dried material was then calcined at 450℃ for 3h in a N2 atmosphere to obtain the modified high-nickel cathode material.
[0194] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 O2 and a coating layer, the coating layer including carbon materials and Co-based oxides, the coating layer thickness is 6.2 nm, and the secondary particle quantity ratio ε is 19%; the high-nickel cathode material has an average particle size of 13.1 μm and a specific surface area of 0.72 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.091 S / cm, and the σ / ε ratio is 0.49. The peel strength σ of the electrode prepared from the high-nickel cathode material is... T180° It is 9.0 mN / mm.
[0195] Example 10
[0196] Unlike Example 1, (5) 50g of the first precursor and 60g of the second precursor were added together to 70ml of deionized water. The mixture was stirred rapidly at 500r / min for 0.5h at room temperature, and then slowly stirred at 30r / min for 2h. The mixed solution in the reactor was then filtered for 20min. The collected solid part was dried at 100℃ for 30h. The dried material was then calcined at 450℃ for 3h in a N2 atmosphere to obtain the modified high-nickel cathode material.
[0197] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 O2 and a coating layer, the coating layer including carbon materials and Co-based oxides, the coating layer thickness is 6.3 nm, and the secondary particle quantity ratio ε is 20%; the high-nickel cathode material has an average particle size of 13.6 μm and a specific surface area of 0.75 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.097 S / cm, and the σ / ε ratio is 0.49. The peel strength σ of the electrode prepared from the high-nickel cathode material is... T180° It is 9.4 mN / mm.
[0198] Comparative Example 1
[0199] (1) Weigh an appropriate amount of LiOH and Ni as a mixture of nickel-cobalt precursor in a molar ratio of 1.04:1. 0.90 Co 0.10 (OH)2, and according to Ni 0.90 Co 0.10 The mass ratio of Al(OH)2 to Al(OH)3 is 78:1. Weigh an appropriate amount of Al(OH)3, mix the three powders, and then pulverize and grind them to obtain a mixture.
[0200] (2) The mixture was calcined in a muffle furnace at 550°C for 4 hours, ground into fine particles, and then transferred to a tube furnace for high-temperature sintering in an oxygen atmosphere for 14 hours. The sintering temperature was controlled at 750°C. The sintered matrix material was then pulverized to D... 50 The particle size is approximately 11 μm. The pulverized material is stored in a polyethylene plastic bag and sealed with aluminum-plastic film.
[0201] (3) Add 100ml of deionized water to a stirrable water-washing reactor and add 50g of matrix material while stirring. Stir for 3 hours. Then filter for 20 minutes. Collect the solid part and dry it at 100℃ for 30 hours. Then calcine the dried material at 450℃ for 3 hours in N2 atmosphere to obtain high-nickel cathode material.
[0202] The high-nickel cathode material obtained in this comparative example is Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 The O2 high-nickel cathode material has an average particle size of 10.6 μm and a specific surface area of 0.81 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The electrical conductivity of the powder under pressure is 0.050 S / cm, and the peel strength σ of the electrode prepared from the high-nickel cathode material is... T180° It is 5.1 mN / mm.
[0203] like Figure 3b As shown, the high-nickel cathode material obtained in this comparative example has a dispersed particle distribution, with no secondary particles. The few seemingly connected particles are actually caused by particle stacking, unlike... Figure 3a Secondary particles in the middle.
[0204] Comparative Example 2
[0205] (1) Weigh an appropriate amount of LiOH and Ni as a mixture of nickel-cobalt precursor in a molar ratio of 1.04:1. 0.90 Co 0.10 (OH)2, and according to Ni 0.90 Co 0.10 The mass ratio of Al(OH)2 to Al(OH)3 is 78:1. Weigh an appropriate amount of Al(OH)3, mix the three powders, and then pulverize and grind them to obtain a mixture.
[0206] (2) The mixture was calcined in a muffle furnace at 550°C for 4 hours, ground into fine particles, and then transferred to a tube furnace for high-temperature sintering in an oxygen atmosphere for 14 hours. The sintering temperature was controlled at 750°C. The sintered matrix material was then pulverized to D... 50 The particle size is approximately 11 μm. The pulverized material is stored in a polyethylene plastic bag and sealed with aluminum-plastic film.
[0207] (3) Add tris(hydroxymethyl)aminomethane (Tris reagent) to a stirrable water-washing reactor and stir to form a solution (pH 8.5). Then add the matrix material and stir for 0.5 h. Weigh 0.45 g of dopamine hydrochloride and dissolve it in the above suspension. Stir for 1 h. Then add 30 ml of aqueous solution containing 1.5 g of cobalt nitrate and continue stirring for 2 h. After that, filter for 20 min to obtain the first precursor.
[0208] (4) The first precursor was added to deionized water and stirred rapidly at 500 r / min for 0.5 h at room temperature, followed by slow stirring at 30 r / min for 2 h. The mixed solution in the reactor was then filtered for 20 min, and the collected solid part was dried at 100 °C for 30 h. The dried material was then calcined at 450 °C for 3 h in an N2 atmosphere to obtain the modified high-nickel cathode material.
[0209] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 O2 and a coating layer, the coating layer including C and Co-based oxides, the coating layer thickness is 5.9 nm, the high-nickel cathode material has an average particle size of 10.9 μm and a specific surface area of 0.76 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The electrical conductivity of the powder under pressure is 0.060 S / cm, and the peel strength σ of the electrode prepared from the high-nickel cathode material is... T180° It is 5.8 mN / mm.
[0210] Comparative Example 3
[0211] (1) Weigh an appropriate amount of LiOH and Ni as a mixture of nickel-cobalt precursor in a molar ratio of 1.04:1. 0.90 Co 0.10 (OH)2, and according to Ni 0.90 Co 0.10 The mass ratio of Al(OH)2 to Al(OH)3 is 78:1. Weigh an appropriate amount of Al(OH)3, mix the three powders, and then pulverize and grind them to obtain a mixture.
[0212] (2) The mixture was calcined in a muffle furnace at 550°C for 4 hours, ground into fine particles, and then transferred to a tube furnace for high-temperature sintering in an oxygen atmosphere for 14 hours. The sintering temperature was controlled at 750°C. The sintered matrix material was then pulverized to D... 50 The particle size is approximately 11 μm. The pulverized material is stored in a polyethylene plastic bag and sealed with aluminum-plastic film.
[0213] (3) Add tris(hydroxymethyl)aminomethane (Tris reagent) to a stirrable water-washing reactor and stir to form a solution (pH 8.5) in 70 ml of deionized water. Then add the matrix material and stir for 0.5 h. Weigh 0.45 g of dopamine hydrochloride and dissolve it in the above suspension. Stir for 1 h. Then add 30 ml of an aqueous solution containing 0.9 g of 2-methylimidazole and continue stirring for 2 h. After that, filter for 20 min to obtain the second precursor.
[0214] (4) Add the second precursor to 70 ml of deionized water, stir rapidly at 500 r / min for 0.5 h at room temperature, then stir slowly at 30 r / min for 2 h, then filter the mixed solution in the reactor for 20 min, collect the solid part and dry it at 100 °C for 30 h, then calcine the dried material at 450 °C for 3 h in N2 atmosphere to obtain the modified high nickel cathode material.
[0215] The high-nickel cathode material obtained in this embodiment includes the matrix material Li. 1.01 Ni 0.88 Co 0.10 Al 0.02 O2 and a coating layer, the coating layer including carbon material, the coating layer thickness is 6.2 nm, the high-nickel cathode material has an average particle size of 11.1 μm and a specific surface area of 0.78 m². 2 / g; the high-nickel cathode material at 8kN / cm 2 The powder conductivity under pressure is 0.068 S / cm, and the peel strength σ of the electrode prepared from high-nickel cathode material is... T180° It is 5.3 mN / mm.
[0216] Performance testing:
[0217] (1) Alkaline impurity test of high-nickel cathode material:
[0218] The content of alkaline impurities on the surface of high-nickel materials is a characteristic of the material surface, which can be quantitatively measured by analyzing the reaction products between the surface and water. When high-nickel material powder is immersed in water, a surface reaction occurs. During the reaction, the pH of the water increases (as the alkaline impurities dissolve), and the alkaline content is quantified by pH titration. The titration result is the alkaline impurity content. The alkaline impurity content can be measured as follows: 5.0 g of high-nickel material powder is immersed in 100 ml of deionized water and stirred for 10 minutes in a sealed glass flask. After stirring to dissolve the alkali, the suspension of powder in water is filtered to obtain a clear solution. Then, 90 ml of the clear solution is titrated with 0.1 M HCl at a rate of 0.5 ml / min while stirring, by recording the pH curve until the pH reaches 3. A reference voltage curve is obtained by titrating a suitable mixture of LiOH and Li₂CO₃ dissolved in deionized water at low concentrations. In almost all cases, two distinct plateaus are observed. The upper plateau with an endpoint y₁ (in ml) between pH 8 and 9 is the equilibrium OH group. - / H2O, followed by balancing CO3. 2- / HCO3 - The lower plateau with an endpoint y2 (in ml) between pH 4 and 6 is HCO3. - / H2CO3. The inflection point y1 between the first and second plateaus and the inflection point y2 after the second plateau are obtained by the corresponding minimum values of the derivative dpH / dVol of the pH curve. The second inflection point is generally close to pH 4.7. The results are then expressed as weight percentages of LiOH and Li2CO3 as shown in equations (1) and (2) below:
[0219]
[0220]
[0221] (2) Methods for observing and testing the microstructure of powder particles in high-nickel cathode materials:
[0222] The thickness of the coating layer was measured using the built-in scale of a transmission electron microscope (TEM) at a magnification of 50k-100k. (3) Test method for the specific surface area of high-nickel cathode materials:
[0223] Using Micromeritics Tristar II, the adsorption capacity under different equilibrium pressures was obtained through N2 adsorption tests and calculations, resulting in isothermal adsorption curves, which were then used to calculate the specific surface area of the cathode material.
[0224] (4) Test method for particle size of high-nickel cathode material:
[0225] The particle size distribution range of the composite cathode material was tested using a Malvern laser particle size analyzer.
[0226] (5) The proportion of secondary particles in high-nickel cathode materials
[0227] Take 50g of sample and observe it under a scanning electron microscope (model S-4800). Divide it into 10 portions. Under 500x magnification, the SEM can show the ratio of the number of secondary particles with interconnected structures in the field of view of all intact particles to the total number of intact particles in the field of view. Calculate the average value of the 10 samples.
[0228] (6) Powder conductivity of high-nickel cathode materials
[0229] A resistivity meter (Suzhou Jinglü Electronics ST-2255A) was used. A 5g powder sample was taken and subjected to constant pressure of 8000kg ± 2kg using an electronic press, maintained for 15-25s. The sample was then placed between the electrodes of the meter. The sample height was h (cm), the voltage across the sample was U, the current was I, and the resistance was R (kΩ). The area of the pressed powder sheet was S = 3.14cm². 2 The electronic conductivity of the powder is calculated using the formula δ=h / (S*R) / 1000, with units of S / m.
[0230] (7) Peel strength of positive electrode sheet
[0231] Weigh 0.8g of high-nickel cathode material, 0.1g of conductive carbon black, and 0.1g of polyvinylidene fluoride and place them in a ball mill jar. Add 15mL of N-methylpyrrolidone and ball mill to form a uniform slurry. Then, uniformly coat the slurry onto aluminum foil and vacuum dry at 80℃ for 12h to obtain the cathode sheet.
[0232] The peel strength of the prepared positive electrode sheet was measured by a tensile testing instrument. Specifically, the single-sided electrode sheet was cut into strips of 25mm*200mm. The test side was bonded to a steel plate with double-sided tape (30mm wide). The electrode sheet was parallel to the steel plate and rolled back and forth 3 times with an automatic roller press. The steel plate with the electrode sheet attached was inserted into the lower clamp of the SHIMADZU peel testing machine and fixed vertically. The electrode sheet current collector was inserted into the upper clamp and fixed, so that the electrode sheet attached to the adhesive tape was at 180° with the electrode sheet fixed in the upper clamp. After the test sample was fixed, the test was started at a peel rate of 100mm / min. 3-5 samples were recorded for each material and the average value was taken.
[0233] (8) Battery formation
[0234] First, the battery is formed with a voltage range of 2.5-4.25V and left to stand for 24 hours; then it is charged at a constant current of 0.01C for 30 minutes; then at a constant current of 0.02C for 30 minutes; and finally charged at a constant current of 0.2C for 4 hours or until the voltage is ≥3.85V, and then left to stand for 12 hours.
[0235] (9) Battery capacity assessment
[0236] Voltage range 2.5-4.25V, 0.2C constant current charging to voltage ≥4.25V, constant voltage charging to current ≤50μA, rest for 10min; 0.2C constant current discharging to voltage ≤2.5V, rest for 10min; 0.5C constant current charging to voltage ≥4.25V, constant voltage charging to current ≤50μA, rest for 10min; 0.5C constant current discharging to voltage ≤2.75V, rest for 12h.
[0237] (10) Battery Cycling
[0238] The voltage range is 2.5-4.25V, and it is cycled 100 times at 0.5C charge and 0.1C discharge, 0.5C discharge, 1C discharge, 2C discharge and 5C discharge respectively.
[0239] (11) DCIR test (voltage range: 2.5V~4.25V, test temperature: 25℃)
[0240] Let it rest for 30 minutes; charge at 1 / 3C constant current until the voltage is ≥4.25V, then charge at constant voltage until the current is ≤0.005C; let it rest for 30 minutes; discharge at 1 / 3C constant current until the voltage is ≤2.5V; cycle 100 times. Record the voltage Ua at the beginning of each discharge cycle and the voltage Ub at the 60th second, and the discharge current I. Dis DC internal resistance calculation: R = (Ua - Ub) / I Dis
[0241] Table 1. Comparison of electrochemical performance data between the examples and comparative examples.
[0242]
[0243] As shown in Table 1, based on the test data from Examples 1 to 8, the high-nickel cathode material has a coating layer on its substrate surface. This coating layer comprises a composite of transition metal oxides and carbon materials, which prevents direct contact between the substrate material and the electrolyte, effectively reducing residual alkali on the material surface and improving the interfacial stability of the cathode material coating. The presence of the coating layer increases the conductivity of the substrate material and enhances the lithium-ion migration rate. Furthermore, some high-nickel cathode materials are connected by carbon materials in the coating layer to form secondary particles, which significantly reduces interparticle contact resistance, thereby improving the electronic and lithium-ion conductivity of the high-nickel cathode material, reducing overpotential in the battery electrodes, and thus synergistically enhancing the cycle performance, rate performance, mitigating gas generation, and reducing the DC impedance of the cathode material. Therefore, the presence of the coating layer and some secondary particles can exert a maximum synergistic effect, significantly improving the electrochemical performance of the high-nickel cathode material, and significantly enhancing the battery's capacity and rate performance.
[0244] As shown in Table 1, compared with the high-nickel cathode material prepared in Example 1, the cathode material prepared in Comparative Example 2 has better rate performance, capacity and cycle performance. This is because no coordination reaction occurred during the preparation process of Comparative Example 2. The surface coating layer of the high-nickel cathode material has a composite of carbon material and Co-based oxide, but there is no interconnection structure between the particles, and secondary particles cannot be formed. The interfacial contact resistance between the particles of the cathode material increases, which is not conducive to improving the rate performance and cycle performance of the material.
[0245] Similarly, in Comparative Example 3, no coordination reaction occurred during the preparation process, and the surface coating of the high-nickel cathode material was a carbon material, specifically Li. + The cathode material prepared in Comparative Example 3 is a non-conductor and also lacks interconnection structure between particles, resulting in high interparticle contact resistance. Compared with Example 1, the cathode material prepared in Comparative Example 3 also shows deterioration in rate capability, capacity, and cycle performance.
[0246] like Figure 4 and Figure 5 As shown, the powder conductivity of the high-nickel cathode material in Example 1 is significantly higher than that in Comparative Example 1. Furthermore, the capacity retention rate after 100 cycles at a high temperature of 45°C is also better than that in Comparative Example 1. This is because the high-nickel cathode material in Example 1 has a coating layer, which can avoid direct contact between the substrate material and the electrolyte, effectively reduce the residual alkali on the material surface, and improve the interfacial stability of the cathode material coating. Its cycle performance is significantly better than that of the uncoated Comparative Example 1.
[0247] Table 2 Comparison of residual alkali test results between the examples and the comparative examples
[0248]
[0249] As shown in Table 2, the residual alkali in Example 1 was significantly lower than that in Comparative Example 1, indicating that co-coating can significantly reduce the residual alkali on the material surface. To further verify the effect of the coating layer, the cathode materials prepared in Example 1 and Comparative Example 1 were placed in an atmospheric environment for a certain period of time. The residual alkali in the material of Example 1 did not change significantly and remained at a low level, while the residual alkali in the cathode material prepared in Comparative Example 1 increased significantly over time, indicating that the coated high-nickel cathode material has good storage performance.
[0250] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A high-nickel cathode material, characterized in that, The high-nickel cathode material includes: Base material, the chemical general formula of which is Li a Ni x Co y M z N b O2, where 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, x+y+z=1, 0≤b<0.4, M is Mn and / or Al, N includes at least one of Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba and Ta; and A coating layer at least partially located on the surface of the substrate material, the coating layer comprising a composite comprising an oxide of a transition metal and a carbon material, the transition metal comprising at least one of Co, Ni and Zn; In this process, at least some of the high-nickel cathode material particles are connected by C-C conjugated π bonds in the coating layer to form secondary particles, and the proportion of the secondary particles in the high-nickel cathode material is ε, where 12% < ε < 36%.
2. The high-nickel cathode material according to claim 1, characterized in that, The material includes at least one of the following features (1) to (4): (1) The thickness of the coating layer is 2nm~15nm; (2) At least a portion of the oxide of the transition metal is embedded in the carbon material having a porous structure; (3) The coating layer is a composite; (4) The carbon material includes at least one of amorphous carbon material and graphitized carbon material.
3. The high-nickel cathode material according to claim 1 or 2, characterized in that, The high-nickel cathode material includes at least one of the following features (1) to (4): (1) CO3 in the high-nickel cathode material 2- The mass content of the high-nickel cathode material is P1wt%, and the CO3 content of the high-nickel cathode material after standing in air for 7 days is... 2- The mass content is P2wt%, and 1 <P2 / P1<3; (2) The high-nickel cathode material at 8kN / cm 2 The electrical conductivity of the powder under pressure is σS / cm, 0.3 < σ / ε < 0.6, and σ > 0.06; (3) The specific surface area of the high-nickel cathode material is 0.2 m². 2 / g ~1.8m 2 / g; (4) The average particle size D of the high-nickel cathode material 50 The size ranges from 8μm to 25μm.
4. A method for preparing the high-nickel cathode material according to any one of claims 1 to 3, characterized in that, Includes the following steps: Two mixed solutions containing dopamine hydrochloride, a base material and a solvent are prepared, wherein the general chemical formula of the base material is Li a Ni x Co y M z N b O2, wherein 0.95≤a≤1.1, 0.6≤x<1, 0<y<0.4, 0<z<0.4, x+y+z=1, 0<b<0.4, M is Mn and / or Al, and N includes at least one of Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba and Ta; A solution containing transition metal ions is added to one portion of the mixed solution, and after thorough mixing, solid-liquid separation is performed to obtain a first precursor; an organic ligand is added to another portion of the mixed solution, and after thorough mixing, solid-liquid separation is performed to obtain a second precursor; and A mixture of the first precursor and the second precursor is added to an aqueous solution for a coordination reaction. The reaction product is then dried and sintered under a protective atmosphere to obtain a high-nickel cathode material.
5. The preparation method according to claim 4, characterized in that, It meets at least one of the following technical features: (1) The average particle size D of the matrix material 50 The thickness ranges from 9μm to 18μm. (2) The mass ratio of the matrix material to the solvent in the mixed solution is 1:(0.5~3); (3) The mass ratio of the matrix material to dopamine hydrochloride in the mixed solution is 1:(0.01~0.4); (4) The solvent includes at least one of water, methanol, ethanol and ethylene glycol; (5) The mixed solution also includes tris(hydroxymethyl)aminomethane; (6) The mixed solution also includes tris(hydroxymethyl)aminomethane, and the mass ratio of tris(hydroxymethyl)aminomethane to dopamine hydrochloride is (0.01~0.2):1; (7) The pH value of the mixed solution is 8~8.
5.
6. The preparation method according to claim 4, characterized in that, It meets at least one of the following technical features: (1) The transition metal ions include Co 2+ Ni 2+ and Zn 2+ At least one of them; (2) The solution containing transition metal ions includes at least one of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt fluoride, cobalt bromide, cobalt iodide, cobalt oxalate, and cobalt sulfate; (3) The mass ratio of the solution containing transition metal ions to the dopamine hydrochloride is (30-80):1, and the mass content of transition metal ions in the solution containing transition metal ions is 1%~10%; (4) The organic ligand includes at least one of 2-methylimidazolium, 2,5-dihydroxyterephthalic acid and dimethyl 2,5-dioxo-1,4-phthalate; (5) The organic ligand is 2-methylimidazole, and the mass ratio of 2-methylimidazole to dopamine hydrochloride is (1~4):1; (6) The mixing temperature is 10℃~30℃; (7) The mixing time is 0.1h to 5h; (8) The solid-liquid separation method includes at least one of filtration and centrifugation.
7. The preparation method according to claim 5 or 6, characterized in that, It meets at least one of the following technical features: (1) The coordination reaction takes 1 h to 8 h; (2) The temperature of the coordination reaction is 40℃~80℃; (3) The mass ratio of the first precursor to the second precursor is 1:(0.8~1.2); (4) The step of washing the first precursor and the second precursor with water respectively includes adding the first precursor and the second precursor to water respectively, controlling the first stirring rate to 300 r / min to 600 r / min and stirring and washing for 0.1 h to 3 h, and controlling the second stirring rate to 10 r / min to 100 r / min and stirring and washing for 0.1 h to 5 h; (5) The total mass of the first precursor and the second precursor to the weight ratio of water is 1:(0.5~3); (6) The drying temperature is 100℃~300℃, and the drying time is 10h~30h; (7) The sintering temperature is 300℃~600℃, and the sintering time is 1h~6h; (8) The protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton and xenon.
8. The preparation method according to claim 4, characterized in that, The method further includes Ni x Co y M z oxides or Ni x Co y M z Hydroxide and lithium source are mixed to obtain a mixture, and the mixture is sintered to obtain a matrix material, wherein M is Mn and / or Al.
9. The preparation method according to claim 8, characterized in that, It meets at least one of the following technical features: (1) The mixing conditions for obtaining the mixture are: dry grinding at 10℃~50℃ for 0.3h~2h; (2) The sintering conditions for obtaining the matrix material are as follows: the mixture is pre-sintered at 400℃~600℃ for 3h~9h in an oxygen-containing atmosphere, and then sintered at 650℃~950℃ for 8h~16h. (3) The sintering conditions for obtaining the matrix material are as follows: the mixture is pre-sintered at 400℃~600℃ for 3h~9h in an oxygen-containing atmosphere, and then sintered at 650℃~950℃ for 8h~16h, wherein the mass content of oxygen in the oxygen-containing atmosphere is ≥95%; (4) The lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate; (5) The amount of lithium source added is such that the ratio of the total molar content of Ni, Co and M to the molar content of Li is 1:(0.95~1.1). (6) The mixture further includes a compound containing doped element N, wherein N includes at least one of Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba and Ta; (7) The mixture further includes a compound containing doped element N, wherein N includes at least one of Zr, W, Mg, Ti, Ce, Sr, V, Mo, Y, Nb, B, S, Ba and Ta, and the compound containing doped element N includes at least one of oxides of N and hydroxides of N. (8) The mixture also includes a compound containing doped element N, wherein the amount of the compound containing doped element N is such that the ratio of the total molar content of Ni, Co and M to the molar content of N is 1:(0~0.4).
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes a positive electrode sheet, which includes the high-nickel positive electrode material according to any one of claims 1 to 3 or the high-nickel positive electrode material prepared by the preparation method according to any one of claims 4 to 9.
Citation Information
Patent Citations
PDA-assisted metal oxide-coated high-nickel ternary layered positive electrode material and preparation method thereof
CN111211305A